A review of interactive narrative systems and technologies: a training perspective. (February 2015) - Luo, Linbo; Cai, Wentong; Zhou, Suiping; Lees, Michael; Yin, Haiyan
As an emerging form of digital entertainment, the interactive narrative has attracted great attention from researchers over the past decade. Recently, there has been an emerging trend to apply interactive narratives to training and simulation. An interactive narrative system allows players to proactively interact with simulated entities in a virtual world and have the ability to alter the progression of a storyline. In simulation-based training, the use of an interactive narrative system enables the possibility to offer engaging, diverse and personalized narratives or scenarios for different training purposes. This paper provides a review of interactive narrative systems and technologies from a training perspective. Specifically, we first propose a set of key requirements in developing interactive narrative systems for simulation-based training. Then we review nine representative existing systems with respect to their system architectures, features and related mechanisms. To examine their applicability to training, we investigate and compare the reviewed systems based on the functionalities and modules that support the proposed requirements. Furthermore, we discuss some open research issues on the future development of interactive narrative technologies for training applications.